Exploring Questioning Strategies in Improving Students’ Reading Comprehension in Narrative Text - Ad Diniyah, Ma’rifatu; Jati, Sigit Pramono; Nikmah, Lailatun (ICONELT, 2024)
This study explores the questioning strategies of class 8A students' reading comprehension of narrative texts at SMPN 10 Gresik. Qualitative descriptive approaches were employed with data gathering procedures through classroom observations, semi-structured interviews with teachers, a group discussion with students, and examination of students' reflective journals. The research results suggest that the questioning method is beneficial in boosting students' reading comprehension of narrative texts, fostering critical thinking and active involvement. Challenges faced include variances in pupils' levels of knowledge and challenges in crafting appropriate questions. In addition, suitable questioning strategies help bridge the gap between students' knowledge and the new concepts being given, thereby enhancing students' understanding and curiosity. In conclusion, the use of proper questioning strategies is highly crucial in building an engaging and inclusive learning environment, which in turn can increase the quality of learning and student understanding.